2015
DOI: 10.1098/rsif.2015.0429
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in intervertebral disc degeneration and regeneration

Abstract: Intervertebral disc (IVD) degeneration is one of the major causes of low back pain, a problem with a heavy economic burden, which has been increasing in prevalence as populations age. Deeper knowledge of the complex spatial and temporal orchestration of cellular interactions and extracellular matrix remodelling is critical to improve current IVD therapies, which have so far proved unsatisfactory. Inflammation has been correlated with degenerative disc disease but its role in discogenic pain and hernia regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(125 citation statements)
references
References 46 publications
6
119
0
Order By: Relevance
“…Although several clinical trials have suggested that inhibition of TNF-α may have considerable promise in the treatment of LBP and radicular pain, challenges remain to be resolved with this monotherapy. A degenerative IVD is in a chronic inflammatory state, and many proinflammatory cytokines such as TNF-α, IL-1β, and IL-6 are involved in the process [85]. The net result of these cytokine networks is to cause an imbalance between catabolism and anabolism within the disc, leading to its degeneration, herniation, and radicular pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several clinical trials have suggested that inhibition of TNF-α may have considerable promise in the treatment of LBP and radicular pain, challenges remain to be resolved with this monotherapy. A degenerative IVD is in a chronic inflammatory state, and many proinflammatory cytokines such as TNF-α, IL-1β, and IL-6 are involved in the process [85]. The net result of these cytokine networks is to cause an imbalance between catabolism and anabolism within the disc, leading to its degeneration, herniation, and radicular pain.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that inflammation plays a critical role in the pathology of IDD [85,86]. In addition to affecting ECM homeostasis, TNF-α can stimulate IVD cells to synthesize many pro-inflammatory cytokines, thereby further aggravating the inflammatory state within the discs.…”
Section: Tnf-α Amplifies the Inflammatory Responsesmentioning
confidence: 99%
“…Physiological mechanical loading can restore the biochemical properties of both tissues, while underloading and overloading reduce tissue function (Gawri et al, 2014;Setton and Chen, 2006;Verteramo and Seedhom, 2007;Wang et al, 2013). ECM turnover is regulated by MMPs and ADAMTS and it is affected by age and degeneration, as the ability of cartilaginous tissues to maintain the ECM declines when both factors increase (Francuski et al, 2014;Illien-Junger et al, 2010;Le Maitre et al, 2004;Molinos et al, 2015;Pauli et al, 2011;Sztrolovics et al, 1997;Wuertz et al, 2009;Yin and Xia, 2014). The effect of osmolarity on the turnover of articular cartilage and IVD ECM is well documented (Amin et al, 2011;Ishihara et al, 1997;Johnson et al, 2014;Wuertz et al, 2007).…”
Section: Trp Channels In Joint Diseasesmentioning
confidence: 99%
“…The breakdown of ECM products during IDD is thought to elicit a proinflammatory response with mechanisms that are dependent on the context and inducing agent [15][16][17]. In response to infection, plasma and leucocytes are recruited to the affected site to activate other cell types whereas in response to tissue injury a vascular response is also instigated, a process that is more complex in avascular tissue [16].…”
Section: Introductionmentioning
confidence: 99%
“…In response to infection, plasma and leucocytes are recruited to the affected site to activate other cell types whereas in response to tissue injury a vascular response is also instigated, a process that is more complex in avascular tissue [16]. Cytokines, such as interleukin (IL)-1β, are thought to be mediators in the breakdown of ECM [4,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%